Obstructive sleep apnoea and nocturnal gastroesophageal reflux are common in lung transplant patients - Shepherd, K.; Chambers, D.; Gabbay, E.; Hillman, D.; Eastwood, Peter (Wiley-Blackwell Publishing Asia, 2008)
Background and objective: Gastroesophageal reflux (GOR) has been implicated in the pathogenesis of bronchiolitis obliterans syndrome (BOS), possibly due to pulmonary aspiration of refluxed acid. Risk of aspiration of gastric contents is increased during sleep due to decreased oesophageal clearance mechanisms and may be further increased by the presence of OSA. This study investigated the relationship between nocturnal GOR, OSA and BOS in a group of lung transplant patients. Methods: Fourteen lung transplant patients underwent overnight polysomnography with simultaneous dual oesophageal pH monitoring. Results: Patients had an FEV1 of 84 ± 15% of their best post-transplant FEV1. Six of the 14 patients were in various stages of BOS. The average proportion of time spent overnight with a pH of <4 was 1.7 ± 3.1%. Increased GOR was evident in 8/14 patients during the postprandial period and/or overnight in the distal and/or proximal oesophagus. All patients had OSA (AHI >5 events per hour). There were no relationships between severity of OSA or GOR and severity of BOS. Conclusion: Both nocturnal GOR and OSA were common in this group of patients but their occurrences were not related. Neither was there any relationship between the presence of nocturnal GOR or OSA and severity of BOS. © 2008 The Authors.